X-Ray photoelectron spectroscopy studies of graphite powder and multiwalled carbon nanotubes covalently modified with Fast Black K: evidence for a chemical release mechanism via electrochemical reduction - Wildgoose, G; Lawrence, N; Leventis, H; Jiang, L; Jones, T; Compton, R (2005)
The development of new materials from which to construct controlled chemical-release systems has been an active area of research for the past four decades. Using X-ray photoelectron spectroscopy (XPS) we demonstrate that graphite powder and multiwalled carbon nanotubes (MWCNTs) covalently derivatised with 2,5-dimethoxy-4-[4-(nitrophenyl)azo]benzenediazonium chloride (FBK) or a derivative of FBK are important new micro and nano-scale materials for use as voltammetrically controlled chemical-release reagents in applications where the small size of the material is advantageous. By examining the N1s and O1s regions of the XPS spectra we can identify functionalities within the FBK moiety as well as hydroxyl, quinonyl and carboxylic acid functional groups present on the carbon surface. Comparison of the XPS spectra of the FBK derivatised carbon (FBK carbon) and FBK derivatised MWCNTs (FBK-MWCNTs) before and after electrochemical reduction reveals that cleavage of the azo-linkage within the FBK moiety occurs upon reduction in aqueous solution. The voltammetric cleavage of the azo-linkage induces chemical release of 1,4-phenylenediamine from the carbon surface, demonstrating the proof of concept for these novel materials. It is envisaged that derivatives of these materials could be used in vivo in a wide range of areas including medical diagnosis and targeted drug-delivery systems as well as in in vitro applications such as analytical chemistry, sensor technology and industrial process monitoring and control. © The Royal Society of Chemistry 2005.